The role of vinyl sulfonic acid homopolymer in calcium oxalate crystallization - Kirboga, Semra; Oner, Mualla (ELSEVIER, 2010)
In this study, the effect of water soluble homopolymer of vinylsulfonic acid on spontaneous crystallization of calcium oxalate (CaOx) was investigated. CaOx crystals exhibiting different shapes and phase structures were produced in the presence of polymer. While the crystal growth of calcium oxalate was inhibited by homopolymer, the morphology of calcium oxalate transformed from monohydrate to dihydrate. Inhibition of calcium oxalate crystallization was provided by adsorption of homopolymer onto the active growth sites of crystals on account of the charge and hydrophilic effects. Polyelectrolyte effects were interpreted in terms of the adsorption of inhibitors onto the active growth sites on the crystal surface. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Crystal growth; Adsorption; Crystallization; Biomineralization; CRYSTAL-GROWTH; KIDNEY-STONE; MONOHYDRATE; INHIBITION; MONOLAYERS; POLYELECTROLYTES; SURFACE; AGGREGATION; MORPHOLOGY; DIHYDRATE; Biophysics; Chemistry; Materials Science